White Light Emission and Judd-Ofelt Analysis of Dy 3+ Doped Mixed Alkali Borate Glass for W-LEDs Material - N. Jarucha; Y. Ruangtaweep; Poomirat Nawarat; Paisan Kanthang; Pichet Limsuwan; H. J. Kim; J. Kaewkhao; Thanapong Sareein (Integrated ferroelectrics, 2023)
The Dy3+ doped lithium sodium potassium borate glasses with white light-emitting were prepared by the melt quenching technique. In this work, optical, photoluminescence properties and Judd-Ofelt analysis of borate glasses have been investigated. For optical properties, Dy3+ doped glasses showed the absorption in visible and near-infrared region, which originate from 6H15/2 ground state to higher state. While the luminescence properties of Dy3+ doped glasses, the emission spectra were presented more intense at 484 nm (blue light) and 574 nm (yellow light) which are essential for white light emitting materials, whilst decay time decrease with an increase of Dy2O3 contents. The emission intensity of Dy3+ doped glasses were enhanced by adding Dy2O3 concentrations until 0.5 mol%, after that the emission intensities were decreased due to the concentration quenching effect. Judd-Ofelt is analyzed by using the absorption and photoluminescence results, The stimulated emission cross-section has been investigated in this work. The CIE 1931 chromaticity investigation shows that Dy3+ doped glass emitted light with white color. Hence, these glasses may be suitable candidates for use in W-LEDs material.
Keywords: Glass properties and applications; Luminescence Properties of Advanced Materials; Phase-change materials and chalcogenides